A Comparative Study of Early Childhood Teachers’ Readiness to Implement Inclusive Education in Urban and Rural Indonesia - Aufa Wulandari; Riana Mashar; Dewi Eko Wati; Iyan Sofyan; Nordin Bin Mamat; Maria Meredith (Jurnal Pendidikan Progresif, 2026)
Geographical differences between urban and rural areas are often assumed to influence teachers’ readiness to implement inclusive education for young children. Inclusive education requires teachers to be prepared in terms of knowledge, skills, and attitudes to accommodate the diversity of children’s learning needs. This study aims to analyze and compare the readiness levels of early childhood education (PAUD) teachers to implement inclusive education in these two contexts. The study employs a comparative descriptive design with the population comprising all PAUD teachers in Indonesia. The sample comprised 200 respondents, including 66 teachers from urban areas and 134 from rural areas.  Data were collected using a structured questionnaire that measured three dimensions of readiness, with a reliability coefficient of 0.968, indicating very high internal consistency. Data analysis was conducted using the Mann–Whitney U test to identify differences between groups. As an additional analysis, ANCOVA was performed to examine the effect of age on teacher readiness, and a Chi-square test was conducted to examine the relationship between inclusive education training experience and teachers' readiness category. These findings suggest that geographic location does not significantly influence the level of readiness of early childhood education teachers in implementing inclusive education. Descriptively, teachers in rural areas had a slightly higher mean score (102.79) than those in urban areas (95.84), but the difference was not statistically significant. These results imply that geographical setting does not significantly affect teacher preparedness. ANCOVA results indicated that age had a significant effect on teacher readiness. The Chi-square test also showed no significant association between training participation and teachers' readiness category. Based on these findings, it can be concluded that the readiness of early childhood education teachers for inclusive education is relatively similar in urban and rural areas. This study was limited to measuring differences by geographic context; therefore, other factors that could influence teacher readiness were not analyzed and require further investigation. Kata kunci: early childhood, inclusive education, teacher readiness.